2020
DOI: 10.1002/agg2.20125
|View full text |Cite
|
Sign up to set email alerts
|

Automated detection of phenological transitions for yellow flowering plants such as Brassica oilseeds

Abstract: Monitoring crop phenology is crucial for making site‐specific management decisions for crop protection and nutrition. The prominent yellow bloom associated with canola (Brassica napus L.) and similar yellow‐flowering plants can provide cues about spatial differences as well as timing of crop input requirements. The objective of this study was to remotely characterize the phenological development of Brassicaceae oilseeds such as canola and carinata (B. carinata A. Braun) in terms of spectral‐temporal dynamics b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Due to a number of additional factors (e.g., in-field variability of growing conditions, presence of parasites/disease agents, spectral signal of canopies rather than single plants, and shadows from overlapping plants), field phenotyping requires a slightly different approach to automated tracking of flowering in rapeseed. However, similar to our findings, the blue and green spectral bands of RGB images (e.g., used to calculate the normalized difference yellowness index, NDYI) have proven to be the most useful for distinguishing between flower and overall canola canopy signals in field settings (Sulik and Long, 2020).…”
Section: Flower Phenotyping/growth Stagessupporting
confidence: 85%
“…Due to a number of additional factors (e.g., in-field variability of growing conditions, presence of parasites/disease agents, spectral signal of canopies rather than single plants, and shadows from overlapping plants), field phenotyping requires a slightly different approach to automated tracking of flowering in rapeseed. However, similar to our findings, the blue and green spectral bands of RGB images (e.g., used to calculate the normalized difference yellowness index, NDYI) have proven to be the most useful for distinguishing between flower and overall canola canopy signals in field settings (Sulik and Long, 2020).…”
Section: Flower Phenotyping/growth Stagessupporting
confidence: 85%
“…However, a few studies have applied comparable approaches to detect and map the spatial distribution of other plant species such as A. saligna, canola, Eucalyptus spp., etc. [11,13,24,58]. The method presented here shows the utility of high spatial resolution drone images acquired during the flowering events of H. subaxillaris over selected areas for the training and validation of landscape-scale models.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this, early-stage winter canola was mapped based on SAR images at the early-bolting stage, with F-score of 0.76 and OA of 79.23% in 2017(Figure 8). Some studies have found that red, green, blue and NIR bands can be effectively used for winter canola mapping during the flowering stage [13,40,41]. Previous studies have mainly explored the features of winter canola at the flowering stage, but rarely explored the early-stage features of winter canola.…”
Section: Important Features For Winter Canola Mappingmentioning
confidence: 99%